Neurosteroids: current perspective in therapy of neuropsychiatric disorders - Tolety, Spandana Bharadwaj; Maity, Nivedita; V., Anuradha H. (International Journal of Basic & Clinical Pharmacology, 2019)
Neurosteroids are natural or synthetic steroid derivatives which act locally in brain by modulating neuronal excitability. The objective of this study is to analyze available literature on classification, biosynthesis and mechanism of action, and therapeutic potential of neurosteroids. A review of literature pertaining to neurosteroids published from inception to 2018 was carried on data bases like PUBMED, Google Scholar and Science Direct. The search terms used were neurosteroids, neuro-active steroids, ganaxolone and GABA-A receptor modulators. Review of literature suggests neurosteroids are powerful neuro-modulators, involving rapid non-genomic and non-hormone receptor mechanisms. They are classified based on structure as pregnane, androstane and sulphated neurosteroids, and based on function as excitatory or inhibitory neurosteroids. They act via GABAA receptor (primarily), rho- GABA (ρGABA), NMDA-glutamate and sigma receptor modulation. The inhibitory neurosteroids demonstrate sedative, anxiolytic and anticonvulsant actions, whereas the excitatory agents produce memory enhancing and anxiogenic effects. They show efficacy in various CNS and psychiatric conditions like epilepsy, anxiety, depression, learning and memory disorders and substance abuse. Endogenous neurosteroids have limited clinical use due to low bioavailability, lack of specificity and unwanted effects. Hence, synthetic agents like alphaxalone, ganaxolone, sepranolone and brexanolone which have better bioavailability and specificity, are being investigated in various phases of clinical trials. Neurosteroids are novel endogenous compounds with neuro-modulatory function and show promising effects in therapy of various neurological and psychiatric conditions. Further studies that prove their long term efficacy and safety may revolutionize the clinical approach to therapy of these conditions.